Kompleks Inferioritas dan Transformasi Psikologis Zainuddin dalam Tenggelamnya Kapal Van der Wijck: Kajian Psikoanalisis Freud-Adler - Rasyid, Yulianti; Putra, Ravito Ardia (Faculty of Languages and Arts, Universitas Negeri Padang, 2025)
This study analyzes Zainuddin's inferiority complex and psychological transformation in Tenggelamnya Kapal Van der Wijck through a synthesis of Freud's psychoanalysis and Adler's individual psychology. The objectives of this study include: (1) identifying the sources of Zainuddin's suffering and low self-esteem, which are intertwined with social rejection of his mixed identity, (2) mapping the id-ego-superego conflicts that accompany romantic relationships and normative demands, and (3) explaining sublimation as a mechanism that transforms inner wounds into creative energy. The research uses a descriptive qualitative method with close reading of narratives and dialogues that show symptoms of inferiority, intrapsychic conflict, and defense strategies. The results show that social stigma triggers feelings of worthlessness that reinforce intrapsychic conflict; this conflict is then transferred through sublimation into artistic production and social achievement, thereby transforming Zainuddin from a passive figure into a productive and influential one. These findings confirm that the tragedy of the shipwreck serves as both the peak of suffering and a trigger for new meanings that consolidate the character's transformation, thereby enriching the reading of literary psychology by making sublimation an operational link between the Freud–Adler frameworks.